[OA166] A1M is a potential kidney protector in 177Lu-octreotate treatment of neuroendocrine tumours. (August 2018) - Andersson, Charlotte; Shubbar, Emman; Åkerström, Bo; Gram, Magnus; Forssell-Aronsson, Eva
Abstract : Treatment of patients with neuroendocrine tumours (NET) using 177 Lu-octreotate has resulted in prolonged survival and improved quality of life, but low cure rate. The treatment is limited by side effects on normal tissues, where kidneys and bone marrow are the major risk organs. Alpha-1-microglobulin (A1M) is an antioxidant with the ability to protect normal tissues from oxidative stress. A1M has recently shown beneficial effects on renal function after 177 Lu-octreotate treatment in preclinical studies. When introducing a radiation protector in radiation therapy it is crucial to maintain high therapeutic effect on tumour tissue. Purpose: To investigate if A1M affects the uptake of 177 Lu in tumour tissue, and/or affects the treatment effect of 177 Lu-octreotate in NET-bearing mice. Methods: Study 1) The biodistribution of 177 Lu-octreotate was studied in BALB/c mice bearing GOT2 tumours (human medullary thyroid carcinoma). The mice were i.v. injected with 5 MBq 177 Lu-octreotate, and half of the mice also received 5 mg/kg A1M. The mice were killed 1 h to 7 days after treatment. The activity concentration in tumour and normal tissues was measured and compared between the two groups. Study 2) The effect of A1M on tumour volume was studied on BALB/c mice bearing GOT1 tumours (human small intestine neuroendocrine tumour). The mice were divided into three groups and treated with: 30 MBq 177 Lu-octreotate or 5 mg/kg A1M or both combined (30 MBq 177 Lu-octreotate and 5 mg/kg A1M). The tumour volume was followed over time and compared between the groups. Results: Study 1) Overall, the biodistribution of 177 Lu-octreotate was similar between the two groups. Study 2) No decrease in mean tumour volume in GOT1 bearing mice treated with A1M alone was observed. For both groups treated with 177 Lu-octreotate, a strong tumour response was observed during the first 14 days after treatment, with a mean volume reduction of about 50%. Thereafter, the tumours re-grew with a similar growth rate for both groups. Conclusions: A1M showed no negative effects on the biodistribution of 177 Lu-octreotate or on the therapeutic response of 177 Lu-octreotate, indicating that A1M is a good candidate for kidney protection during treatment with 177 Lu-octreotate, and should be further investigated.